2013
DOI: 10.4081/or.2013.e7
|View full text |Cite
|
Sign up to set email alerts
|

Spinal posture and pelvic position in three hundred forty-five elementary school children: a rasterstereographic pilot study

Abstract: Children's posture has been of growing concern due to observations that it seems to be impaired compared to previous generations. So far there is no reference data for spinal posture and pelvic position in healthy children available. Purpose of this pilot study was to determine rasterstereographic posture values in children during their second growth phase. Three hundred and forty-five pupils were measured with a rasterstereographic device in a neutral standing position with hanging arms. To further analyse fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…The absence of influence of age on spine curvatures is in agreement with results published by others [13] [14] in adults, and in children [15]. In contrast, Youdas et al [16] reported an effect of age on standing lumbar curvatures in persons between 20 and 79 years of age, but this effect was only significant when comparing the age group of 20 to 29 years with the age group of 50 to 59 years.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of influence of age on spine curvatures is in agreement with results published by others [13] [14] in adults, and in children [15]. In contrast, Youdas et al [16] reported an effect of age on standing lumbar curvatures in persons between 20 and 79 years of age, but this effect was only significant when comparing the age group of 20 to 29 years with the age group of 50 to 59 years.…”
Section: Discussionsupporting
confidence: 91%
“…Rasterstereography, a spine and surface topography technique, can be used to measure such changes in children. In a previous rasterstereographic study of 345 children between 8 and 11 years, a mean kyphotic angle of 47.1°± 7.5 and a mean lordotic angle of 42.1°± 9.9 was found (Furian, Rapp, Eckert, Wild, & Betsch, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…Body posture was assessed using the Diers Formetric III 4D optoelectronic method. The method allows photogrammetric video registration of the back surface using a raster stereography process [9][10][11]. Based on the obtained data, a precise three-dimensional model of the back surface was created [12].…”
Section: Body Posture Examinationmentioning
confidence: 99%